PENGARUH K3 DAN FASILITAS KERJA TERHADAP PRODUKTIVITAS KERJA MELALUI KEPUASAN KERJA PADA PT. ELNUSA TBK - Simamora, Riduan Ofstevenly; Sembiring, Edison Cholia; Ramli, Soehatman (Universitas Bina Taruna Gorontalo, 2025)
The aim of this research is to analyze and examine the impact of Occupational Health and Safety (OHS) and Work Facilities on Job Satisfaction and their subsequent effect on Work Productivity at PT. Elnusa Tbk Field Sanga-Sanga. This study employs a quantitative research approach using a survey method and causal statistical analysis through Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). Data collection was carried out using a non-probability sampling method with an incidental sampling technique. The sample for this study consists of at least 93 employees from PT. Elnusa Tbk Field Sanga-Sanga. The results indicate that Occupational Health and Safety (OHS) and Work Facilities have a positive and significant impact on Job Satisfaction. Furthermore, Occupational Health and Safety (OHS) and Work Facilities also have a positive and significant effect on Work Productivity, while Job Satisfaction significantly influences Work Productivity.